2016
DOI: 10.4204/eptcs.202.6
|View full text |Cite
|
Sign up to set email alerts
|

A multi-paradigm language for reactive synthesis

Abstract: This paper proposes a language for describing reactive synthesis problems that integrates imperative and declarative elements. The semantics is defined in terms of two-player turn-based infinite games with full information. Currently, synthesis tools accept linear temporal logic (LTL) as input, but this description is less structured and does not facilitate the expression of sequential constraints. This motivates the use of a structured programming language to specify synthesis problems. Transition systems and… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
2
1

Relationship

3
5

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 76 publications
0
14
0
Order By: Relevance
“…The computations were performed on a 32 core AMD Opteron machine at 2.4GHz with 96 GB of RAM, and and we see considerable gains in computation time for the parallelized approach. The implementation is written in Python using the packages dd, omega [15], and tulip [14]. 1 A possible explanation for the large variance is the cost of reordering the BDDs, which can show large variance depending on the structure of the formula for which the reordering is being done.…”
Section: Methodsmentioning
confidence: 99%
“…The computations were performed on a 32 core AMD Opteron machine at 2.4GHz with 96 GB of RAM, and and we see considerable gains in computation time for the parallelized approach. The implementation is written in Python using the packages dd, omega [15], and tulip [14]. 1 A possible explanation for the large variance is the cost of reordering the BDDs, which can show large variance depending on the structure of the formula for which the reordering is being done.…”
Section: Methodsmentioning
confidence: 99%
“…Slugs turns off reordering during strategy construction. Filippidis et al [9] reported better performance with reordering during strategy construction. We are not aware of any GR(1) specific heuristics for (dynamic) BDD variable ordering.…”
Section: Related Workmentioning
confidence: 98%
“…For this purpose, we implemented the exact symbolic minimization method for the lattice of integer orthotopes (hypperrectangles aligned to axes). The implementation is available as part of the Python package omega [149]. Briefly, the problem of finding a minimal DNF formula of the form we described can be expressed as in Fig.…”
Section: Generating Minimal Specificationsmentioning
confidence: 99%